Molecular Characterization and Expression Profiles of Cryptochrome Genes in a Long-Distance Migrant, Agrotis segetum (Lepidoptera: Noctuidae). Issue 1 (23rd January 2019) - Chang, Hong; Guo, Jiang-Long; Fu, Xiao-Wei; Wang, Meng-Lun; Hou, You-Ming; Wu, Kong-Ming
Abstract: Cryptochromes act as photoreceptors or integral components of the circadian clock that involved in the regulation of circadian clock and regulation of migratory activity in many animals, and they may also act as magnetoreceptors that sensed the direction of the Earth's magnetic field for the purpose of navigation during animals' migration. Light is a major environmental signal for insect circadian rhythms, and it is also necessary for magnetic orientation. We identified the full-length cDNA encoding As-CRY1 and As-CRY2 in Agrotis segetum Denis and Schiffermaller (turnip moth (Lepidoptera: Noctuidae)). The DNA photolyase domain and flavin adenine dinucleotide-binding domain were found in both cry genes, and multiple alignments showed that those domains that are important for the circadian clock and magnetosensing were highly conserved among different animals. Quantitative polymerase chain reaction showed that cry genes were expressed in all examined body parts, with higher expression in adults during the developmental stages of the moths. Under a 14:10 (L:D) h cycle, the expression of cry genes showed a daily biological rhythm, and light can affect the expression levels of As-cry genes. The expression levels of cry genes were higher in the migratory population than in the reared population and higher in the emigration population than in the immigration population. These findings suggest that the two cryptochrome genes characterized in the turnip moth might be associated with the circadian clock and magnetosensing. Their functions deserve further study, especially for potential control of the turnip moth.